Prescription Opioids. IV: Disposition of Hydrocodone in Oral Fluid and Blood Following Single-Dose Administration - Cone, Edward J.; DePriest, Anne Z.; Heltsley, Rebecca; Black, David L.; Mitchell, John M.; LoDico, Charles; Flegel, Ron (Journal of analytical toxicology, 2015)
The Substance Abuse and Mental Health Services Administration (SAMHSA) is currently evaluating hydrocodone (HC) for inclusion in the Mandatory Guidelines for Federal Workplace Drug Testing Programs. This study evaluated the time course of HC, norhydrocodone (NHC), dihydrocodeine (DHC) and hydromorphone (HM) in paired oral fluid and whole blood specimens by liquid chromatography–tandem mass spectrometry (limit of quantitation = 1 ng/mL of oral fluid, 5 ng/mL of blood) over a 52-h period. A single dose of HC bitartrate, 20 mg, was administered to 12 subjects. Analyte prevalence was as follows: oral fluid, HC > NHC > DHC; and blood, HC > NHC. HM was not detected in any specimen. HC was frequently detected within 15 min in oral fluid and 30 min in blood. Mean oral fluid to blood (OF : BL) ratios and correlations were 3.2 for HC (r = 0.73) and 0.7 for NHC (r = 0.42). The period of detection for oral fluid exceeded blood at all evaluated thresholds. At a 1-ng/mL threshold for oral fluid, mean detection time was 30 h for HC and 18 h for NHC and DHC. This description of HC and metabolite disposition in oral fluid following single-dose administration provides valuable interpretive guidance of HC test results.